Ultrasonic evaluation of the physical and mechanical properties of granites - Vasconcelos, Graça (2008)
Masonry is the oldest building material that survived until today, being used all over the world and being present in the most impressive historical structures as an evidence of spirit of enterprise of ancient cultures. Conservation, rehabilitation and strengthening of the built heritage and protection of human lives are clear demands of modern societies. In this process, the use of nondestructive methods has become much common in the diagnosis of structural integrity of masonry elements. With respect to the evaluation of the stone condition, the ultrasonic pulse velocity is a simple and economical tool. Thus, the central issue of the present paper concerns the evaluation of the suitability of the ultrasonic pulse velocity method for describing the mechanical and physical properties of granites (range size between 0.1-4.0 mm and 0.3-16.5 mm) and for the assessment of its weathering state. The mechanical properties encompass the compressive and tensile strength and modulus of elasticity, and the physical properties include the density and porosity. For this purpose, measurements of the longitudinal ultrasonic pulse velocity with distinct natural frequency of the transducers were carried out on specimens with different size and shape. A discussion of the factors that induce variations on the ultrasonic velocity is also provided. Additionally, statistical correlations between ultrasonic pulse velocity and mechanical and physical properties of granites are presented and discussed. The major output of the work is the confirmation that ultrasonic pulse velocity can be effectively used as a simple and economical nondestructive method for a preliminary prediction of mechanical and physical properties, as well as a tool for the assessment of the weathering changes of granites that occur during the serviceable life. This is of much interest due to the usual difficulties in removing specimens for mechanical characterization.